Beneficial and toxic effects of REE in algae and plants - Ashraf, Nermeen (Jihočeská univerzita, 2022)
Lanthanides mainly represented by REE are the most frequently occurring elements as compared to arsenic and lead. REE consist of a group of elements associated with each other in terms of common physical and chemical properties, with studies concerning phytoremediation and physiological effects of such elements on living biota, is important to be addressed as these elements are frequently being considered as emerging pollutants because of excessive mining and release into the environment. Very important is to study the toxic effects of lanthanum in microalgae under environmental conditions. Experimental trials are evaluating especially potential risks on growth and photosynthesis under nanomolar-dose, with promising decrease and acute toxicity. To this end, the two most promising La-binding protein is currently investigated in green microalgae (Desmodesmus quadricauda) with high affinities. Subcellular localization patterns of La have been also shown to predict possible expression sites and to understand the metabolic response of La in microalgae. We also identify accumulator plant species for LREE in contaminated mining areas for phytoremediation purposes, aim of this study was conducted in the Brazilian mining area for REE and as well as identifying the bioavailable content which can help in predicting the promising species. This field study was done for finding new accumulators which are involved in concentrating LREE in above-ground parts. Our study suggests toxic effects of La and identified preferentially good hyperaccumulator plant specie Christella dentata for phytomining of lanthanides. This could be used as a predictive bioaccumulator in phytoremediation and its further analysis can be a part of future studies for insight mechanisms using analytical techniques, involving the identification of La-binding proteins in Desmodesmus quadricauda.
Beneficial and toxic effects of REE in algae and plants
Keywords: lanthanides; microalgae; growth; photosynthesis; La-binding protein; subcellular localization; phytoremediation; LREE; hyperaccumulator; Christella dentata; lanthanides; microalgae; growth; photosynthesis; La-binding protein; subcellular localization; phytoremediation; LREE; hyperaccumulator; Christella dentata